Change in Central Corneal Thickness after Trabeculectomy - PS Mahar, Mustafa Kamal Junejo (Pakistan Journal of Ophthalmology, 2017)
Purpose: To determine the change in central corneal thickness after trabeculectomy. Study design: Prospectiveinterventional study Place and duration of study: Isra postgraduate institute of ophthalmology, Al-Ibrahim eye hospital, Karachi. January 2014 to June 2016 Materials and methods: One hundred Thirty eyes of 113 glaucoma patientswho underwent trabeculectomy were assessed for the change in central corneal thickness from January 2014 to June 2016. The study approval was granted by the institutional Ethical Review committee. Patients’ characteristics, including demographics, clinical details and management were recordedin a detailed Proforma. Results: The mean age of our patients was 53.3 ± 12.3 years (Range 13 to 84 years). The mean CCT before trabeculectomywas 524.25 ±38.53µm. After 12 months follow-up the mean CCT was 521.95 ± 38.25 µm with correlation of 0.855 which was not statistically significant. Conclusion: In our study there was no statistically significant change in central corneal thickness after trabeculectomy at the mean follow-up of 12 months. Keywords: Central Corneal Thickness, Trabeculectomy, Mitomycin C